DIRECTIONS FOR IMPROVING THE ACTIVITIES OF LOCAL SELF- GOVERNMENT BODIES IN UKRAINE IN ENSURING THE RIGHTS, FREEDOMS AND LEGITIMATE INTERESTS OF CITIZENS (Bulletin of criminological association of Ukraine, 2024)
The article states that the issues of improving certain areas of human life have always been one of the most difficult in administrative and legal science, because their comprehension required not only the analysis of theoretical material, but was also associated with the creative process of searching for tools and mechanisms aimed at achieving positive changes in managerial approaches to the organization of certain activities, as well as the development of projects and the adoption of new regulatory legal acts. The areas of improving the activities of local governments in Ukraine in ensuring the rights, freedoms and legitimate interests of citizens include improving the organizational, managerial and regulatory legal framework for the interaction of local governments with other entities providing free primary legal assistance, in particular in the context of the potential for involving legal clinics of higher education institutions in an online format, when scientific and pedagogical workers will provide the necessary legal assistance to territorial communities, physically being tens of kilometers away from them. The need to implement successful and time-tested examples of foreign experience and public opinion was emphasized. It is argued that the development of human resources in territorial communities includes advanced training, various classes, trainings and seminars dedicated to current legal issues in territorial communities and ways to resolve them.
Keywords: areas of improvement; ensuring the rights; freedoms and legitimate interests of citizens; local government bodies; legal aid; interaction; foreign experience; human resources potential